Modelling the steaming of whole wheat grains - Stapley, A; Landman, K; Please, C; Fryer, P (1999)
The heat and moisture treatment of starch is important to food manufacture. In cereal processing, grains must be boiled or streamed for the starch to gelatinise and be digestible. NMR imaging has shown that the moisture content distributions of steamed wheat grains are uniform. Thus, gravimetric data are sufficient the time evolution of the moisture content to be analysed. When steam is taken up by the grain it is ultimately absorbed as liquid water. Since this involves a phase change, the accompanying liberation of latent heat will raise the grain temperature. Thermocouple measurements confirm that the grain temperature is slightly higher than the surrounding steam temperature. A model for the mass and heat transfer is proposed which takes account of the experimental observations. The simplest model predicts the temperature difference between the grain and the surrounding steam to be a linear function of grain moisture content, with the moisture content varying exponentially with time. The model predictions are compared with experimental data, and the values of water activity coefficient, heat and mass transfer coefficients are extracted and compared to values in the literature where available.